Isolation and purification of potential major active antioxidant constituent from Artocarpus heterophyllus J33 variety rind extract - Daud, Mohd Nazrul Hisham; Wibowo, Agustono (Universiti Teknologi MARA (UiTM), 2025)
Artocarpus heterophyllus J33 (AhJ33) is a significant fruit cultivar of A. heterophyllus in Malaysia and is extensively farmed. For commercial purposes, the pulp is typically extracted from the skin, which is generally discarded. The primary aim of this study was to extract and identify the principal antioxidant component from the rind of AhJ33 fruit waste for the purpose of converting it into a food product with high antioxidant potential. The DDPH assay was chosen as the antioxidant assessment method for crude extract, fractions derived from column chromatography, and isolated and purified compounds. The identification and elucidation of the extracted and purified active antioxidant compound were conducted utilizing spectroscopic methods, including Fourier Transform Infrared Spectroscopy (FTIR), Nuclear Magnetic Resonance (NMR), and Liquid Chromatography-Mass Spectrometry (LC-MS). The spectral data indicated that the primary active antioxidant component was identified as 3,4-dihydroxybenzoic acid, generally referred to as protocatechuic acid. The extracted and purified chemical may serve as reference material (RM), potentially aiding in the manufacture of certified reference material (CRM) for quality assurance in future nutraceutical product development, aligning with the waste-to-wealth concept